+0  
 
+1
309
3
avatar+627 

Expand and simplify.

 

(t-1)^3 + 6(t-1)^2 + 12(t-1) + 8

 

Help please. Thanks

supermanaccz  Oct 25, 2017
edited by supermanaccz  Oct 25, 2017
 #1
avatar+91071 
+2

(t-1)^3 + 6(t-1)^2 + 12(t-1) + 8

 

Let's write this in a different manner

 

(t-1)^3  + 8  + 6(t-1)^2 + 12(t-1) 

 

The first two terms can be written as a sum of cubes thusly

 

[ (t - 1) + 2 ]  [ (t - 1)^2  - 2(t - 1)  + 4 ]  =

 

[ t + 1 ] [ t^2 - 2t + 1 - 2t + 2 + 4 ]  =

 

[ t + 1]  [  t^2 - 4t + 7 ]      (1)

 

The second pair of terms can be factored as

 

6 [ t - 1 ] [ t - 1 + 2]  =

 

6 [ t - 1] [t + 1]  =  [ t + 1] [6t - 6]    (2)

 

Putting (1) and (2) together, we have

 

[ t + 1 ]  [  t^2 - 4t + 7 + 6t - 6 ]  =

 

[ t + 1 ]  [ t^2 + 2t + 1 ]  =

 

[  t + 1 ] [t + 1] [t + 1 ]  =

 

[ t + 1]^3

 

 

cool cool cool

CPhill  Oct 25, 2017
 #2
avatar+20150 
+2

Expand and simplify.

(t-1)^3 + 6(t-1)^2 + 12(t-1) + 8

 

Formula:
\([1+(t-1)]^3 = t^3 = (t-1)^3 + 3(t-1)^2+3(t-1) + 1 \)

 

\(\begin{array}{|rcll|} \hline && \mathbf{(t-1)^3 + 6(t-1)^2 + 12(t-1) + 8 } \\ &=& (t-1)^3 + 3(t-1)^2+3(t-1) +1 \\ && \quad + 3(t-1)^2+9(t-1)+7 \\ &=& t^3 + 3(t-1)^2+9(t-1)+7 \\ &=& t^3 + 3(t^2-2t+1)+9t-9+7 \\ &=& t^3 + 3t^2-6t+3+9t-9+7 \\ &=& t^3 + 3t^2+3t+1 \quad & | \quad (1+t)^3 = t^3+3t^2+3t+1 \\ &\mathbf{=}& \mathbf{(1+t)^3} \\ \hline \end{array} \)

 

laugh

heureka  Oct 26, 2017
 #3
avatar+627 
+1

thanks guys! :)

supermanaccz  Oct 28, 2017

11 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.